External affairs : cross-border relations - Dixit, J. N. (Jyotindra Nath), 1936-2005.; Singh, S. K. (Shailendra K.) (New Delhi : Lotus Collection, 2003)
India's foreign relations with South Asia in post-independence era.
Pakistan / S.K. Singh -- Sri Lanka / J.N. Dixit -- Nepal / K.V. Rajan -- China / C.V. Ranganathan -- Afghanistan / M.H. Ansari -- Bangladesh / Deb Mukharji -- Bhutan / Salman Haidar.
Keywords: National security -- India; South Asia -- Foreign relations -- India; India -- Foreign relations -- South Asia; India -- Foreign relations -- 1947-1984.; India -- Foreign relations -- 1984-